NiO/Graphene Composite for Enhanced Charge Separation and Collection in p-Type Dye Sensitized Solar Cell - Yang, H.; Guai, G.; Guo, C.; Song, Q.; Jiang, San Ping; Wang, Y.; Zhang, W.; Li, C. (American Chemical Society, 2011)
A p-type semiconductor photoelectrode in dye sensitized solar cells (DSCs) has a large optical band gap and high ionization potential but suffers from its intrinsically low hole transfer rate, thus resulting in much poorer performance than n-DSCs. Nickel oxide (NiO)/graphene composite is synthesized to offer a larger surface area and higher conductivity than the pristine NiO film. The novel composite as a photoelectrode in p-DSCs demonstrates increment of both short-circuit photocurrent and open-circuit photovoltage, leading to 2 times increase of power conversion efficiency. Electrochemical impedance spectroscopy and open-circuit voltage decay measurements indicate that the charge recombination of the composite-based p-DSCs is significantly suppressed due to enhanced hole transport by the presence of graphene, thus achieving an efficient electronhole pair charge separation and collection in the composite film electrode for performance-improved NiO-based devices. The proposed mechanism provides physical insight into the enhancement process in p-DSCs.